The level of knowledge on the subject of HIV/AIDS among grade 6 and grade 7 learners of Idas Valley Primary School in Stellenbosch - Cornelissen, Shirle (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil) -- Stellenbosch University, 2012.